Revisiting poverty measures towards individualisation - Meulders, Danièle; O’Dorchai, Síle (Journal of Income Distribution®, 2012)
We use the methodology developed in a previous study to individualise all incomes reported in the European Union Statistics on Income and Living Conditions (2006). Based on individual incomes we compute financial-dependency rates which are compared with the household-level at-risk-of-poverty rates defined by the European Commission. The determinants of financial dependency are studied by means of descriptive statistics and by the estimation of bivariate probit regressions for men and women. We cover nine European countries. Finally, four new indicators are proposed to complement the Laeken indicators.